Managing performance evaluation uncertainties in schools: When teachers become struggling performers. (November 2017) - Englund, Hans; Frostenson, Magnus
Performative technologies are increasingly relied upon as a means of controlling the work of teachers. As noted in the literature, one possible outcome of this trend is the performer, a teacher identity that presupposes the internalization of, and adaptation to, a performative logic. Based on the findings from an empirical study of a Swedish upper secondary school, we suggest that teachers who actually submit to the underlying logic of performative technologies – i.e. who intentionally strive towards a performative identity – will encounter a number of performance evaluation uncertainties, due to how performative technologies may: (a) reflect and recognize teacher performances based on qualitative judgements, (b) fail to take into account their entrepreneurial endeavours, (c) depict essentially collective effects as individual performances, and (d) reflect and recognize performances in a relativizing way. Such performance evaluation uncertainties will, in turn, provoke perceived tensions as performative teachers want to be (perceived as) performers but become uncertain as to when and why they did (not) perform well. And importantly, we find that such tensions tend to turn the ongoing reproduction of a performative identity into a cognitive struggle. Based on this, we introduce and elaborate on a particular type of performative teacher identity; the struggling performer .